A Typical Case of "Cross Time" Revision : – The Version Change of Wang Jingzhi’s The Wind of Cymbidium - Ren, Yiran (Transactions on Social Science, Education and Humanities Research, 2024)
Wang Jingzhi’s The Winds of Cymbidium is the first true collection of love poems since the May 4th Movement, and it has had a tremendous impact on the new poetry scene. The poetry collection has changed in the 1922 version, the 1957 version, and the 1992 version. Among them, the texts from the 1922 version and the 1957 version have strong changes. Through reading the complicated variant texts in the original text and the auxiliary text of these two editions, this paper deeply analyzes the important influence of new literary contexts such as social ideology and literary policies and norms on the "cross-time" revision of poetry collections, and analyzes the poets’ aesthetic mentality trajectories in different periods, the ways of coping with The Times, and their gains and losses.